Comparison of musculoskeletal anatomic relationships, determined by magnetic resonance imaging, in postpubertal female patients with and without classic bladder exstrophy. (29th January 2013) - Anusionwu, Ifeanyi; Tekes, Aylin; Stec, Andrew A.; Gearhart, John P.; Wright, E. James
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Several studies in the paediatric literature have characterized the pelvic musculoskeletal anatomy of infants and children with bladder exstrophy using MRI and three‐dimensional CT. The pelvic floor anatomy of female patients with bladder exstrophy who have undergone somatic growth and puberty is less well described. This study uses MRI to characterize comprehensively the pelvic anatomy of postpubertal females with classic bladder exstrophy by measuring 15 pelvic floor variables previously described in younger children with bladder exstrophy. Objective To characterize pelvic musculoskeletal anatomy in postpubertal females with classic bladder exstrophy, and to compare this with females without bladder exstrophy. Patients and Methods The authors reviewed the medical records of all females in our institutional review board‐approved bladder exstrophy database of 1078 patients and identified those with classic bladder exstrophy who underwent pelvic magnetic resonance imaging (MRI) after the age of 12 years. Indications for MRI included haematuria, adnexal lesion, perineal fistula, non‐pelvic cancer staging, abdominal wall hernia and vaginal stenosis. Age‐ and race‐matched female patients without exstrophy who underwent MRI evaluation for similar indications were included for comparison. The MRI protocol included axial, sagittal and coronal T1‐ and/or T2‐weighted imaging. Results The study included 30 patients with a median (range) age of 22.5 (12–55) years at time of MRI. Ten patients had bladder exstrophy while 20 control patients did not. A smaller percentage of levator ani was located in the anterior compartment of the pelvis in patients with bladder exstrophy compared with controls. The iliac wing angle, puborectalis angle, ileococcygeous angle, levator ani width, symphyseal diastasis, erectile body diastasis, posterior bladder neck distance and posterior anal distance was greater in patients with bladder exstrophy than in those without. The ischial angle and obturator internus angle were narrower in patients with bladder exstrophy than in those without, and there was no significant difference between levator ani surface area, sacral anal angle, sacral bladder neck angle and bladder neck erectile body distance between the two patient groups. Conclusions In postpubertal females with bladder exstrophy, significant deviations from normal pelvimetry exist, including posterior location of the majority of the levator ani muscle, a wider ileococcygeous angle and a wider symphyseal diastasis. These differences are similar to those described in previous comparisons of younger children with bladder exstrophy and control children.